FIELD EXPERIENCE AND THE READINESS OF PRE-SERVICE PRIMARY TEACHER EDUCATION STUDENTS TO TEACH ENGLISH: A SYSTEMATIC REVIEW - Rifhani Handayani L; Faidah Yusuf (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to examine how field experience supports the readiness of pre-service primary school teachers in PGSD programs to teach English. A Systematic Literature Review was conducted by identifying empirical studies published between 2015 and 2025 through ERIC, Google Scholar, Semantic Scholar, ResearchGate, and institutional repositories. The screening followed PRISMA procedures, with inclusion criteria focusing on generalist pre-service teachers’ teaching field experiences and exclusion of studies involving in-service or English-major pre-service teachers. Data from the selected studies were synthesized based on five analytical dimensions: pedagogical competence, teaching self-efficacy, understanding of primary classroom contexts, lesson-planning skills, and overall readiness to teach English to young learners. The review found that field experience contributes positively to classroom management, instructional adaptation, confidence building, contextual awareness, and gradual improvement in planning skills. However, these benefits were inconsistent due to uneven mentoring quality, weak school–university coordination, and limited opportunities for structured reflection. Importantly, field experience alone was insufficient to ensure readiness for English teaching, as PGSD students lacked exposure to TEYL-focused coursework and sufficient English proficiency. The findings suggest that strengthening curricular support, mentoring systems, and TEYL integration is essential to optimize field experience in preparing PGSD pre-service teachers to teach English effectively.